The design and application of an intensive care unit point-of-care nursing handover checklist based on the situation, background, assessment, and recommendation technique - Wang, Lei; Ma, Yu-Jie; Chen, Xiao-Ting; Zhang, Jie; Liu, Tao (Frontiers in Public Health, 2022)
Objective: This study aims to analyze the effect of using an intensive care unit point-of-care nursing handover checklist based on the situation, background, assessment, and recommendation (SBAR) communication technique. Methods: An intensive care unit point-of-care nursing handover checklist was designed based on the SBAR technique, and standard point-of-care nursing handover procedures and effect assessment indicators were established to compare the occurrence of adverse handover events and nursing risks with those previously observed. Results: Before and after the application of the intensive care unit point-of-care SBAR checklist, the occurrence of missed items during the handover was 7.26% and 2.02%, inadequate preparation for handover was 28.33% and 5%, and nursing risks were 5% and 1.67%, respectively. Conclusion: Based on the SBAR technique, the application of an intensive care unit point-of-care nursing checklist reduced the occurrence of adverse handover events and nursing risks.